Особливості застосування електросудомної терапії при наркологічній патології = Features of the application of electroconvulsive therapy in the treatment of drug abuse pathology - Chugunov, V. V.; Kurilo, V. A.; Danilevska, N. V. (Journal of Education, Health and Sport, 2016)
Чугунов В. В., Курило В. О., Данілевська Н. В. Особливості застосування електросудомної терапії при наркологічній патології = Features of the application of electroconvulsive therapy in the treatment of drug abuse pathology Journal of Education, Health and Sport. 2016;6(9):893-901. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.162962 http://ojs.ukw.edu.pl/index.php/johs/article/view/3953 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016. Особливості застосування електросудомної терапії при наркологічній патології В. В. Чугунов, В. О. Курило, Н. В. Данілевська Запорізький державний медичний університет МОЗ України FEATURES OF THE APPLICATION OF ELECTROCONVULSIVE THERAPY IN THE TREATMENT OF DRUG ABUSE PATHOLOGY V. V. Chugunov, V. A. Kurilo, N. V. Danilevska Zaporizhzhya State Medical University Ministry of Healthcare of Ukraine Summary Objective: to examine the possibility of electroconvulsive therapy (ECT) use for the treatment of patients with addiction to psychoactive substances (PAS). The algorithm of ECT, which consists of 3 stages and IX sub-stages is given. The study of the therapeutic viability of ECT in the case of broad spectrum of addictive pathology (F10-F19) in the context of the relief of addictive attraction to PAS and comorbid disorders, including emotional disorders and resistant to pharmacotherapy of pain syndrome is made. ЕСТ is an effective method for additions therapy and comorbide psychopathological states. High therapeutic effect is connected with sanogenetic effect achieved in stopping of poorly curable pathology and achievement of sustained remission even in the cases where other methods are noneffective. Key words: addiction, substance abuse, drug addiction, alcoholism, electroconvulsive therapy